2019
DOI: 10.3390/foods8090395
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Characterization of Grape Skins and Seeds of Four Italian Red Cultivars at Harvest and after Fermentative Maceration

Abstract: Agro-industry byproducts can still contain large amounts of phenolic compounds, and one of the richest sources are grape skins and seeds as grape pomace, both fermented (red winemaking) and unfermented (white winemaking). The residual polyphenolic content depends on various factors such as grape variety, vintage, and winemaking technique. In this work, four red grape varieties cultivated in northern Italy were studied: Albarossa, Barbera, Nebbiolo, and Uvalino. The work was aimed at studying the polyphenolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
57
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 53 publications
13
57
2
1
Order By: Relevance
“…Among different grape peels cultivars, Barbera and Albarossa presented higher anthocyanins and lower vanillin-reactive flavans and condensed tannins amounts compared to Nebbiolo and Uvalino varieties, whereas grape seeds from Barbera and Albarossa varieties had smaller quantities of vanillin-reactive flavans, proanthocyanidins, and condensed tannins compared to Nebbiolo and Uvalino, these differences disappearing after fermentative processes application (Guaita & Bosso, 2019).…”
Section: Polyphenolic Profile Of Grape Byproductsmentioning
confidence: 90%
See 1 more Smart Citation
“…Among different grape peels cultivars, Barbera and Albarossa presented higher anthocyanins and lower vanillin-reactive flavans and condensed tannins amounts compared to Nebbiolo and Uvalino varieties, whereas grape seeds from Barbera and Albarossa varieties had smaller quantities of vanillin-reactive flavans, proanthocyanidins, and condensed tannins compared to Nebbiolo and Uvalino, these differences disappearing after fermentative processes application (Guaita & Bosso, 2019).…”
Section: Polyphenolic Profile Of Grape Byproductsmentioning
confidence: 90%
“…In others, the increase of the absorbance occurs during the reaction of the antioxidant with the chromogenic reagent, for example, ferric reducing antioxidant power and cupric reducing antioxidant capacity (Shahidi & Zhong, 2015). Guaita and Bosso (2019) reported higher antioxidant activity of grape seeds compared to peels, underlining a positive correlation with the tannins content. Tkacz et al (2019) revealed that grape seeds have higher antioxidant activity ranging from 207.9 to 479.7 µmol trolox equivalents (TE)/g compared to peels for which it varied from 17.6 to 339.2 µmol TE/g in function of the variety, with higher values for the red ones (Table 3).…”
Section: Antioxidant Propertiesmentioning
confidence: 98%
“…Total contents of proanthocyanidins were determined with vanillin assay [60][61][62]. Standard curve and calibration curve were obtained by measuring absorption of different concentration of standards solution.…”
Section: Spectrophotometric Analysismentioning
confidence: 99%
“…In this context, numerous studies have been conducted in colon cancer cells to investigate the effects of grape extracts on the modulation of cell membrane components and on the viability and metastatic potential [23][24][25]. Grape skin and grape seed extracts are made up of different polyphenolic compounds that elicit multiple beneficial biological activities [26]. The resveratrol is able to accumulate sphingolipids in cell membranes, leading to cell cycle arrest and apoptosis [27].…”
Section: Introductionmentioning
confidence: 99%